Saskia Pronk-Tiethoff: The Germanic Loanwords in Proto-Slavic (= Leiden Studies in Indo-European 20): Amsterdam - New York, NY: Rodopi, 2013. 316 seiten (ISBN 978-90-420-3732-8) - Holzer, Georg (Slavia Centralis, 2020)
The paper presents the book The Germanic Loanwords and Proto-Slavic, published in 2013.